TINJAUAN YURIDIS TERHADAP PENGADAAN TANAH BAGI KEPENTINGAN UMUM DI KOTA SAMARINDA BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2012 TENTANG PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM - Muhammad Fachryan Nugraha (Universitas 17 Agustus 1945 Samarinda, 2021)
AbstractLand acquisition for public use often experiences problems in the procurement process. The problem is that on one hand, the need for land in the context of development is so urgent while on the other hand the land supply is limited. This study aims to determine the suitability of land acquisition for public use in Samarinda City with Law Number 2 of 2012 concerning Land Procurement for Development in the Public Interest, and suitability of awarding compensation to holders of land rights with Law Number 2 of the Year 2012 concerning Land Procurement for Development in the Public Interest. This type of research used in the writing of this law is empirical juridical research which in essence examines the applicable legal provisions and what happens in the reality of society. The research approach used is descriptive which aims to provide a specific description or explanation of the state of the object or problem under study. The results of the study concluded that land acquisition in samarinda city not in accordance with applicable legal provisions in this case Law Number 2 of 2012 concerning Land Procurement for Development in the Public Interest because there are still obstacles that are often faced by the City Government of Samarinda. In case compensation is in accordance with Law No. 2 of 2012 concerning Land Procurement for Development in the Public Interest. Howiver, there are still disadvantaged citizens because the value of compensation is not sufficient for economic needs, as well as unpaid compensation.